Pemanfaatan Alat Permainan Edukatif dalam Mengembangkan Kemampuan Anak Usia Dini - Liana Lumbantoruan; Ahmad Nasir (Inovasi Pendidikan dan Anak Usia Dini, 2026)
Educational Play Tools (EPT) are learning media designed to support children's development through play activities. Early childhood is a critical period for growth and development, requiring appropriate stimulation to optimize various developmental aspects. This article aims to examine the utilization of Educational Play Tools in developing early childhood abilities. The method used in this article is a literature study by reviewing various books, journals, and scientific articles related to educational play tools and early childhood education. The discussion shows that Educational Play Tools provide significant benefits in developing cognitive, language, physical-motor, social-emotional, and creative abilities of children. Through the use of EPT, children can learn actively, explore their environment, solve problems, communicate effectively, and interact with others in enjoyable learning situations. However, several challenges remain, including limited facilities, lack of teacher competence in utilizing EPT, and insufficient parental involvement in supporting educational play activities. Therefore, collaboration among teachers, parents, and educational institutions is needed to optimize the use of Educational Play Tools. Proper utilization of EPT can support holistic and balanced child development, thereby helping achieve the goals of early childhood education.